Pencil Lead Electrode Modifikasi Lapisan Tipis Emas Untuk Deteksi Formaldehida Secara Voltametri Siklik - Malinda, Tasya; Sari, Trisna Kumala; Nasra, Edi; Azra, Fajriah (Departemen Kimia FMIPA UNP, 2024)
Formaldehyde is a toxic, carcinogenic, mutagenic and genotoxic compound that can harm the human body. Formaldehyde can threaten human health such as, can cause eye, nose and throat irritation and contact dermatitis on the skin. This research aims to study the response of pencil lead electrode (PLE) and pencil lead electrode (PLE) modification with gold thin layer in the development of formaldehyde sensor by using cyclic voltammetry. The electrode modification was done by potential-sweeping electrodeposition of Au on electrode and known as Au/PLE electrode. The resulting electrode has high conductivity and excellent catalytic activity because it is able to provide a large current response. In this study, the optimum conditions will be determined based on variations supporting electrolyte and cycle gold thin layer electrodeposition. Variations in supporting electrolyte and cycle for gold thin layer electrodeposition on the formaldehyde sensor give different peak current and potential results. KOH 0,1 M is supporting electrolyte optimum and cycle for gold thin layer electrodeposition optimum is one cycle.